THE IMPACT OF EMPLOYEE WELLNESS PROGRAMS ON EMPLOYEE PRODUCTIVITY AND RETENTION - Herlina, Erna; Akbar, Barzalius; Raden Suryandi Buwono Cokro; Garin Giffary Hartanto (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the relationship between employee wellness programs and employee productivity and retention levels. Through the literature review method, this study collects and reviews various literature from reputable working paper sources, book chapters, and indexed journal articles. The results of the analysis showed that well-being programs that supported physical, psychological, and work-life balance significantly increased motivation, productivity, and job satisfaction. The study also supports that well-being drives employee retention by reducing burnout and increasing employee engagement and commitment to the organization. The implications of these results recommend the implementation of a comprehensive wellbeing program as an effective strategy in supporting productivity and retaining a talented workforce, so that companies can create a sustainable and competitive work environment